Thrombin and plasmin generation in patients with plasminogen or plasminogen activator inhibitor type 1 deficiency. Issue 6 (30th August 2019) - Saes, Joline L.; Schols, Saskia E. M.; Betbadal, Kathleen F.; van Geffen, Mark; Verbeek‐Knobbe, Kitty; Gupta, Sweta; Hardesty, Brandon M.; Shapiro, Amy D.; van Heerde, Waander L.
Abstract: Introduction: Deficiencies of plasminogen and plasminogen activator inhibitor type 1 (PAI‐1) are rare disorders of fibrinolysis. Current laboratory assays for analysis of activity of plasminogen and PAI‐1 do not provide an accurate correlation with clinical phenotype. Methods: The Nijmegen Hemostasis Assay (NHA) was used to simultaneously measure thrombin and plasmin generation in 5 patients with plasminogen deficiency (PLGD) and 10 patients with complete PAI‐1 deficiency. Parameters analysed included: lag time ratio, thrombin peak time ratio, thrombin peak height, thrombin potential (AUC), fibrin lysis time, plasmin peak height and plasmin potential. Parameters were expressed as a percentage compared to a reference value of 53 healthy normal controls. Results: Patients with PLGD demonstrated a short lag time and thrombin peak time, with normal thrombin peak height but an increased AUC. Plasmin generation was able to be detected in only one (23% plasminogen activity) of the five PLGD patients. All ten PAI‐1 deficient patients demonstrated a short lag and thrombin peak time, low thrombin peak height with normal AUC. Plasmin generation revealed an increased plasmin peak and plasmin potential; interestingly, there was a large variation between individual patients despite all patients having the same homozygous defect. Conclusion: Patients with either PLGD or PAI‐1 deficiency show distinct abnormalities in plasmin and thrombin generation in the NHA. The differences observed in the propagation phase of thrombin generation may be explained by plasmin generation. These results suggest that disorders of fibrinolysis also influence coagulation and a global assay measuring both activities may better correlate with clinical outcome.